QOLP-28. PREOPERATIVE SLEEP DISTURBANCE AND ITS ASSOCIATION WITH QUALITY OF LIFE IN ADULT BRAIN TUMOR PATIENTS. (9th November 2020) - Chen, Pin-Yuan; Chiu, Hsiao-Yean; Lin, Pei-Ching
Abstract: BACKGROUND: Sleep disturbances are common complaints in adult brain tumor patients and impact their quality of life profoundly. The prevalence and pattern of preoperative sleep disturbances are still unknown. MATERIAL AND METHOD: There were 36 adult patients with primary brain tumors who were recruited before craniotomy. All participants completed a battery of questionnaires, including the Athens Insomnia Scale, Epworth Sleepiness Scale, Pittsburgh Sleep Quality Index, Brief Fatigue Inventory, Hospital Anxiety, and Depression Scale, Morningness-Eveningness Questionnaire, and EORTC-QLQ-BN20. Actigraphy was put on a non-dominant wrist for obtaining objective sleep parameters, such as the dichotomy index. RESULT: The prevalence of preoperative insomnia, poor sleep quality, excessive daytimes sleepiness, and circadian disruption were all high but similar between benign and malignant brain tumor groups. Patients with glioma had poorer quality of life. Insomnia was the only sleep disturbance that significantly associated with quality of life in a multivariate linear regression modal. CONCLUSION: Sleep disturbances are common in adult brain tumor patients. Insomnia worse the quality of life of these patients. A further longitudinal investigation of sleep disturbances and quality of life in brain tumor patients is worthful.